Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

|x|+|y|=0? or |x|=-|y|? Both |x| and |y| are positive, so is it possible that |x| is negative of some positive quantity, thus, only possibility would be |x|=|y|=0? and that's the question.

Using (1), |y|=-x/2 or \(x \leq 0\), so, it is possible that x = -1, y = 1/2, then \(|x|+|y| \neq 0\) or x =0, y = 0, then \(|x|+|y| = 0\), Insufficient.

Using (2); |x|=-y/2 or \(y \leq 0\), so, it is possible that y = -1, x = 1/2, then \(|x|+|y| \neq 0\) or y = 0, x = 0, then \(|x|+|y| = 0\), Insufficient.

Combining both, \(x \leq 0\), then |x|=-y/2 implies, -x=-y/2 or 2x = y.......(a)

Similarly, \(y \leq 0\), then |y|=-x/2 implies, -y=-x/2 or x = 2y........(b) From (a) & (b) 4y=y, thus y=0 & x=0 Also, \(|x|+|y| = 0\). Sufficient.

Since absolute value is non-negative the from \(|x| + |y| = 0\) we have that the sum of two non-negative values equals to zero, which is only possible if both of them equal to zero. So, the question basically asks whether \(x=y=0\)

(1) x + 2|y| = 0. It's certainly possible that \(x=y=0\) but it's also possible that \(x=-2\) and \(y=1\). Not sufficient.

Notice that from this statement \(|y|=-\frac{x}{2}\), so \(-\frac{x}{2}\) equals to a non-negative value (\(|y|\)), so \(-\frac{x}{2}\geq{0}\) --> \(x\leq{0}\).

(2) y + 2|x| = 0. It's certainly possible that \(x=y=0\) but it's also possible that \(y=-2\) and \(x=1\). Not sufficient.

Notice that from this statement \(|x|=-\frac{y}{2}\), so \(-\frac{y}{2}\) equals to a non-negative value (\(|x|\)), so \(-\frac{y}{2}\geq{0}\) --> \(y\leq{0}\).

(1)+(2) We have that \(x\leq{0}\) and \(y\leq{0}\), hence equations from the statements transform to: \(x-2y=0\) and \(y-2x=0\). Solving gives \(x=y=0\). Sufficient.

(1) Not sufficient, but implies that x is not positive. (2) Again, not sufficient, but implies y is not positive.

When considering (1) and (2) together, we can add the two equations side-by-side and obtain x + 2|y| + y + 2|x| = 0, and (x + |x|) + |x| + (y + |y|) +|y| = 0 + |x| + 0 + |y| = |x| + |y| = 0. We used the fact that if x is not positive (it is negative or 0), then x + |x| = 0.

Correct answer - C. _________________

PhD in Applied Mathematics Love GMAT Quant questions and running.

Since the Question stem is asking if sum of 2 absolute values (which are positive) equal to 0. We know that sum of 2 positive nos can be zero if both are zero. Hence Question asks if x=y=0

from St1 we have x+2|y|=0 Now if y is less than equal to 0 than we have x-2y=0 or x=2y or x=0 if y is 0 If y>0 then x=-2y

Since using 1 we have more than 1 possible option therefore A,D ruled out

From st 2 we have y+2|x|=0 If x is less than or equal to zero than y-2x=0 or y=2x or if x=0 then y=0 If x>0 then y=-2x

Again more than 1 solution so Option B ruled out

Combining both statement we get

x=2y ,x=-2y, y=2x and y=-2x and x=0, y=0

Since x=0,y=0 is common from both equation we can say say that |x|+|y|=0 Note that x and y have to be 0 to satisfy all above equations. _________________

“If you can't fly then run, if you can't run then walk, if you can't walk then crawl, but whatever you do you have to keep moving forward.”

There are two ways we can solve. One is to get the positive and negative cases of y. On the other hand, we can isolate |y| as the question is looking for the value of |y|+|x|

x + 2|y| = 0 2|y| = -x |y| = -x/2 if |y| = -x/2 then -x/2 must be positive which means x is negative. Of course, x could also be zero meaning we don't know if the absolute value of x and y = 0 INSUFFICIENT

(2) y + 2|x| = 0 This is a similar statement to the above one, except we have the absolute value of x instead of y. y + 2|x| = 0 2|x| = -y |x| = -y/2 As with the above statement -y/2 = an absolute value so y must be negative. However, it could also be = to zero. INSUFFICIENT

So....from 1 and 2 we know that x<=0 and y<=0 which means that: x + 2|y| = 0 x-2y = 0

Since absolute value is non-negative the from \(|x| + |y| = 0\) we have that the sum of two non-negative values equals to zero, which is only possible if both of them equal to zero. So, the question basically asks whether \(x=y=0\)

(1) x + 2|y| = 0. It's certainly possible that \(x=y=0\) but it's also possible that \(x=-2\) and \(y=1\). Not sufficient.

Notice that from this statement \(|y|=-\frac{x}{2}\), so \(-\frac{x}{2}\) equals to a non-negative value (\(|y|\)), so \(-\frac{x}{2}\geq{0}\) --> \(x\leq{0}\).

(2) y + 2|x| = 0. It's certainly possible that \(x=y=0\) but it's also possible that \(y=-2\) and \(x=1\). Not sufficient.

Notice that from this statement \(|x|=-\frac{y}{2}\), so \(-\frac{y}{2}\) equals to a non-negative value (\(|x|\)), so \(-\frac{y}{2}\geq{0}\) --> \(y\leq{0}\).

(1)+(2) We have that \(x\leq{0}\) and \(y\leq{0}\), hence equations from the statements transform to: \(x-2y=0\) and \(y-2x=0\). Solving gives \(x=y=0\). Sufficient.

Hi Bunuel, why do the "equations from the statements transform to: \(x-2y=0\) and \(y-2x=0\)"? Shouldn't it be -x + 2y = 0 and -y +2x = 0? Hope you can help clarify.

Since absolute value is non-negative the from \(|x| + |y| = 0\) we have that the sum of two non-negative values equals to zero, which is only possible if both of them equal to zero. So, the question basically asks whether \(x=y=0\)

(1) x + 2|y| = 0. It's certainly possible that \(x=y=0\) but it's also possible that \(x=-2\) and \(y=1\). Not sufficient.

Notice that from this statement \(|y|=-\frac{x}{2}\), so \(-\frac{x}{2}\) equals to a non-negative value (\(|y|\)), so \(-\frac{x}{2}\geq{0}\) --> \(x\leq{0}\).

(2) y + 2|x| = 0. It's certainly possible that \(x=y=0\) but it's also possible that \(y=-2\) and \(x=1\). Not sufficient.

Notice that from this statement \(|x|=-\frac{y}{2}\), so \(-\frac{y}{2}\) equals to a non-negative value (\(|x|\)), so \(-\frac{y}{2}\geq{0}\) --> \(y\leq{0}\).

(1)+(2) We have that \(x\leq{0}\) and \(y\leq{0}\), hence equations from the statements transform to: \(x-2y=0\) and \(y-2x=0\). Solving gives \(x=y=0\). Sufficient.

Hi Bunuel, why do the "equations from the statements transform to: \(x-2y=0\) and \(y-2x=0\)"? Shouldn't it be -x + 2y = 0 and -y +2x = 0? Hope you can help clarify.

We have that \(x\leq{0}\) and \(y\leq{0}\), thus \(|x|=-x\) and \(|y|=-y\). Therefore \(x + 2|y| = 0\) becomes \(x-2y=0\) and \(y + 2|x| = 0\) becomes \(y-2x=0\).

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email. _________________

Since absolute value is non-negative the from \(|x| + |y| = 0\) we have that the sum of two non-negative values equals to zero, which is only possible if both of them equal to zero. So, the question basically asks whether \(x=y=0\)

(1) x + 2|y| = 0. It's certainly possible that \(x=y=0\) but it's also possible that \(x=-2\) and \(y=1\). Not sufficient.

Notice that from this statement \(|y|=-\frac{x}{2}\), so \(-\frac{x}{2}\) equals to a non-negative value (\(|y|\)), so \(-\frac{x}{2}\geq{0}\) --> \(x\leq{0}\).

(2) y + 2|x| = 0. It's certainly possible that \(x=y=0\) but it's also possible that \(y=-2\) and \(x=1\). Not sufficient.

Notice that from this statement \(|x|=-\frac{y}{2}\), so \(-\frac{y}{2}\) equals to a non-negative value (\(|x|\)), so \(-\frac{y}{2}\geq{0}\) --> \(y\leq{0}\).

(1)+(2) We have that \(x\leq{0}\) and \(y\leq{0}\), hence equations from the statements transform to: \(x-2y=0\) and \(y-2x=0\). Solving gives \(x=y=0\). Sufficient.

I solved this question in the following way - still got the right answer (not sure if I am right or it was just a fluke). Please provide input.

|x| + |y| = 0, means both value of x&y needs to be known (preferably zero)

Each statement talks about two variables at the same time -Both Insufficient- So either C or E

Now, Statement 1 is in form of y=mx+c (m=-0.5/+0.5 - slope) & Statement 2 is in form of y=mx+c (m=-2/+2 - slope)

Since any of the possibilities do not overlap each other, these lines will intersect each other at one point - and thus a solution is possible with the help of both the statements. Thus C

gmatclubot

Re: Is |x| + |y| = 0?
[#permalink]
12 Dec 2015, 22:21

http://blog.ryandumlao.com/wp-content/uploads/2016/05/IMG_20130807_232118.jpg The GMAT is the biggest point of worry for most aspiring applicants, and with good reason. It’s another standardized test when most of us...

I recently returned from attending the London Business School Admits Weekend held last week. Let me just say upfront - for those who are planning to apply for the...